Evaluation of micro esthetics characteristics of maxillary anterior teeth after orthodontic treatment in UCLP: a digital dental model study - Manfio, Aura Sofia Caceres (2017)
Introduction: The purpose of this study was to evaluate in digital models the dental and gingival characteristics composing the anterior micro esthetic of the smile in unilateral cleft lip and palate (UCLP) individuals with missing lateral incisors in the cleft area after comprehensive orthodontic treatment and, to compare the cleft side (CS) with the non cleft side (NCS) and, those measurements with a control group of normal occlusion (NO). Methods: The experimental group included 57 dental casts of patients with UCLP (31 males, 26 females; mean age, 20.4 years) with comprehensive orthodontic treatment associated to canine substitution for the missing maxillary lateral incisor and premolar substitution of the canine. The control group comprised 48 dental casts of noncleft individuals with normal occlusion (NO) (25 males, 23 females; mean age, 16.5 years). The dental and gingival features evaluated included: (1) crown height, (2) crown width, (3) crown width-to-height proportion (Width/Height ratio), (4) mesiodistal dimension of anterosuperior teeth in a frontal perspective (Anterior View Width), (5) incisal edge symmetry between homologous teeth, (6) central-to-lateral incisal step, and central-to-canine incisal step, (7) gingival margin symmetry between homologous teeth, (8) central-to-lateral gingival step, and central-to-canine gingival step, (9) crown angulation and (10) crown inclination. The paired t test was used for intragroup comparisons, and the independent t test was used for intergroup comparisons. After Bonferroni correction the level of significance considered was of p<0.016 for all measurements except width ratio, gingival step, incisal step and angulation (p<0.025). Results: When compared to the NCS, the CS canine substituting the lateral incisor missing had augmented crown height (p<.001) and width (p<.001), the premolar had diminished crown height (p<.001), consequently the width/height ratio for the premolar was altered (p<.001); there was asymmetry between the gingival level of central (p<.001) and lateral incisors (p<.001) and, the central incisor was in a more vertical position (p=.005). Between the CS of UCLP and NO the canine substituting the lateral incisor presented an augmented mesiodistal size (p<.001) and it affected the anterior view width (p<.001). Central and lateral incisors in the C side had higher crown height (p<.001) and the premolar substituting the canine had a diminished crown height (p<.001). Central incisor (p<.001) and lateral incisors (p=.006) were more uprighted and premolars substituting canines had decreased lingual inclination (p=.010). The NCS and the NO had fewer differences, the lateral incisors were slightly wider (p<.001) and the gingival step between central incisor and canine was augmented (p<.001). Tooth vestibular inclination was increased especially in central incisors (p=.012) and canines (p=.004) when compared to the normal occlusion group. Conclusions: Differences were found in the micro esthetics elements that comprises the anterior dental and gingival esthetics between cleft and non cleft sides of UCLP and between UCLP and NO. These differences were more pronounced when considering the cleft side. Therefore, specific esthetic procedures should be performed in cases with canine substitution for missing lateral incisors of UCLP in association with the orthodontic treatment, aiming to provide a more harmonious and natural smile